2019
DOI: 10.3390/su11020500
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Degradation and Thermal Decomposition of Ethylene-Vinyl Acetate (EVA) Polymer-Modified Cement Mortar (PCM) Exposed to High-Temperature

Abstract: A polymer-modified cement mortar (PCM) is widely used as a repair material for reinforced concrete (RC) structures owing to its excellent strength and durability. However, considering the maintenance of the RC structures and the use period of the structures, the change in the physical properties of the PCM should be evaluated when exposed to various high-temperature environments, such as fires. In this study, the degradation of the mechanical properties (compressive strength and modulus of elasticity), thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…The flow table value was increased by 34.7% and 24.6%, respectively, when EVA and PVA replaced 5% of cement. The flow table value was increased by 15.4% when 2.5% of each polymer was used (Results are in agreement with the recent researches by Kim et al 201931 Yang et al 202019 . Polymers might entrain some air.…”
supporting
confidence: 90%
“…The flow table value was increased by 34.7% and 24.6%, respectively, when EVA and PVA replaced 5% of cement. The flow table value was increased by 15.4% when 2.5% of each polymer was used (Results are in agreement with the recent researches by Kim et al 201931 Yang et al 202019 . Polymers might entrain some air.…”
supporting
confidence: 90%
“…Such behavior justifies the use indicated in the bibliography [6], [21], [22], [35], demonstrating performance also as a plasticizer, increasing the consistency. It is noticed that this admixture acts through the entanglement of polymeric molecules, which in high concentrations, and suffering the stresses of the spreading table, fluidized the material [37], explaining the increase in the spreading diameter with the higher dosage of the admixture.…”
Section: Figure 2 Flow-table Resultssupporting
confidence: 61%
“…Its main activities are in improving adhesion, flexural strength, deformability, abrasion resistance, maximizing its use in adhesive mortars, grouts and plasterboards glues. However, studies [21], [22] showed the potential of this admixture for use as water retainer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various forms and types of polymers are used both to modify cement concrete mixtures and to produce polymer-cement concretes (PCC), polymer-impregnated concretes (PIC) and polymer concretes (PC) [20]. In [21], Kim et al presented an application of EVA polymer to the production of polymer-modified cement mortar (PCM), a widely used repair material for reinforced concrete (RC) structures due to its excellent strength and durability. Successful testing of the addition of polymers to cement concrete was described by Gutarowska et al [22] and Shen et al [23].…”
Section: Introductionmentioning
confidence: 99%